Competitive climate adaptation. Italian startups leading the way to climate change adaptation in cities - Pennino, Stella (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban Practices section aims at presenting recent advancements on relevant topics that underline the challenges that the cities have to face. This note provides an overview of the role that innovative climate startups can play in fostering climate adaptation in cities while promoting urban competitiveness, and the strategic support that these entities can provide in managing urban and territorial transformations. The nature of these entities and the role they can play in the governance of urban transformation is outlined, and a brief review of Italian cases is carried out. Finally, the results are discussed, highlighting the potential that these economic constructions have in urban climate adaptation and urban competitiveness, but also the challenges they face. Three significant case studies of startups promoting climate adaptation in urban areas are presented, showing the relevance of the topic and its potential role in the urban adaptation discussion.